2022
DOI: 10.3389/fcimb.2022.987692
|View full text |Cite
|
Sign up to set email alerts
|

Rapid diagnosis of Talaromyces marneffei infection by metagenomic next-generation sequencing technology in a Chinese cohort of inborn errors of immunity

Abstract: Talaromyces marneffei (T. marneffei) is an opportunistic pathogen. Patients with inborn errors of immunity (IEI) have been increasingly diagnosed with T. marneffei in recent years. The disseminated infection of T. marneffei can be life-threatening without timely and effective antifungal therapy. Rapid and accurate pathogenic microbiological diagnosis is particularly critical for these patients. A total of 505 patients with IEI were admitted to our hospital between January 2019 and June 2022, among whom T. marn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 70 publications
1
12
0
Order By: Relevance
“…We report an international retrospective study of talaromycosis in IEI patients, reporting the genetic, immunological, and clinical characteristics of disease. The diseases of talaromycosis with IEI are common in severe combined immunode ciency (IL-2R, ADA) and combined immunode ciency (RELB, CD40L, STAT3), antibody de ciencies (CVID caused by NFKB2 de ciency), intrinsic and innate immunity defects (IL12RB1 de ciency, IFNGR1 de ciency, CARD9, and STAT1-GOF), and autoin ammatory disorders (COPA gene defect), in which XHIM, STAT1-GOF, and HIEs (STAT3-LOF) are the most susceptible diseases for development of IEI-associated talaromycosis [4,11,12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We report an international retrospective study of talaromycosis in IEI patients, reporting the genetic, immunological, and clinical characteristics of disease. The diseases of talaromycosis with IEI are common in severe combined immunode ciency (IL-2R, ADA) and combined immunode ciency (RELB, CD40L, STAT3), antibody de ciencies (CVID caused by NFKB2 de ciency), intrinsic and innate immunity defects (IL12RB1 de ciency, IFNGR1 de ciency, CARD9, and STAT1-GOF), and autoin ammatory disorders (COPA gene defect), in which XHIM, STAT1-GOF, and HIEs (STAT3-LOF) are the most susceptible diseases for development of IEI-associated talaromycosis [4,11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Infections commonly occur in Indonesia and southern China, especially Guangdong, Guangxi, Hong Kong, and Taiwan [1]. T. marneffei causes aggressive infections in immunocompromised patients, especially in patients with HIV diagnosis, anti-IFN-γ autoantibody positivity (AIGA), autoimmune disease, glucocorticoid administration and/or immunosuppression therapy, malignancies, and IEI [3,4]. Diagnosis of talaromycosis is often delayed, or talaromycosis is misdiagnosed as tuberculosis [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that some infected individuals thought to be non-immunosuppressed carry neutralizing anti-IFN-γ autoantibodies and associated HLA alleles (Guo et al, 2020). Additionally some HIV-negative patients have been shown to carry immune-related genetic mutations such as CD40L, STAT1, STAT3 and CARD9 (You et al, 2021;Liu et al, 2022). For this reason, in spite of the fact that there was no evidence suggesting this patient suffered from immune diseases, her immunocompetency remains undetermined.…”
Section: Discussionmentioning
confidence: 99%
“…T. marneffei infections in humans are overwhelming in immunocompromised individuals, however a number of cases in apparent immunocompetent individuals have been described (Duong, 1996;Qiu et al, 2015;Pruksaphon et al, 2022). Increasingly these HIV-negative patients are found to have a variety of other immunocompromising conditions (You et al, 2021;Liu et al, 2022). Clinically, talaromycosis is usually referred to as an easily misdiagnosed, intractable and high-mortality disease, for its uncertain pathogenesis, non-specific symptoms, various imaging manifestations and complicated treatment with serious side effects.…”
Section: Introductionmentioning
confidence: 99%